Cell Intrinsic Galectin-3 Attenuates Neutrophil ROS-Dependent Killing of Candida by Modulating CR3 Downstream Syk Activation - Wu, Sheng-Yang; Huang, Juin-Hua; Chen, Wen-Yu; Chan, Yi-Chen; Lin, Chun-Hung; Chen, Yee-Chun; Liu, Fu-Tong; Wu-Hsieh, Betty A. (Frontiers in Immunology, 2017)
Invasive candidiasis is a leading cause of nosocomial bloodstream infection. Neutrophils are the important effector cells in host resistance to candidiasis. To investigate the modulation of neutrophil fungicidal function will advance our knowledge on the control of candidiasis. While recombinant galectin-3 enhances neutrophil phagocytosis of Candida, we found that intracellular galectin-3 downregulates neutrophil fungicidal functions. Co-immunoprecipitation and immunofluorescence staining reveal that cytosolic gal3 physically interacts with Syk in neutrophils after Candida stimulation. Gal3-/- neutrophils have higher level of Syk activation as well as greater abilities to generate ROS and kill Candida than gal3+/+ cells. While galectin-3 deficiency modulates neutrophil and macrophage activation and the recruitment of monocytes and dendritic cells, the deficiency does not affect the numbers of infiltrating neutrophils or macrophages. Galectin-3 deficiency ameliorates systemic candidiasis by reducing fungal burden, renal pathology, and mortality. Adoptive transfer experiments demonstrate that cell intrinsic galectin-3 negatively regulates neutrophil effector functions against candidiasis. Reducing galectin-3 expression or activity by siRNA or gal3 inhibitor TD139 enhances human neutrophil ROS production. Mice treated with TD139 have enhanced ability to clear the fungus. Our work unravels the mechanism by which galectin-3 regulates Syk-dependent neutrophil fungicidal functions and raises the possibility that blocking gal3 in neutrophils may be a promising therapeutic strategy for treating systemic candidiasis.